دراسة تأثير تقنيات الكشف في نظام SAC-OCDMA على عامل جودة الإشارة باستخدام الـ Optisystem - قداحة هبة; نعمة سوزان (Latakia University Journal -Engineering Sciences Series, 2016)
This research includes a simulation of optical code division multiple access system transceiver (OCDMA) of the spectral amplitude coding (SAC). The study investigates the effect of the pulse generator type used in the transmitter SAC-OCDMA of direct detection technique and the effect of the length of the optical fiber on the signal quality factor (Q) and on the bit error ratio( BER) . In addition a comparison is made between the SAC-OCDMA system of direct detection technique and another one of complementary subtraction technique in terms of signal quality factor and the bit error ratio when using the same parameters for both systems. يتضمن هذا البحث نمذجة ومحاكاة لمرسل ومستقبل نظام العبور المتعدد بتقسيم الكود OCDMA (Optical Code Division Multiple Access) ذو ترميز المطال الطيفي SAC (Spectral Amplitude Coding) حيث تمت دراسة تأثير نوع مولد النبضات المستخدم في مرسل SAC-OCDMA ذي تقنية الكشف المباشر وتأثير طول الليف البصري على عامل جودة الإشارة Q وعلى نسبة خطأ البت BER، كما تم إجراء مقارنة بين نظام SAC-OCDMA ذو تقنية الكشف المباشر وآخر ذو تقنية الطرح التكميلي من حيث عامل جودة الإشارة Q ونسبة خطأ البت BER عند استخدام نفس البارامترات للنظامين.